High-value valorization of Periplaneta americana residue: intestinal health regulation in pre-bred hens and circular economy applications - Tao, Sicai; Zi, Shunyi; Yan, Liangjing; Yang, Mei; Zhao, Tianzhang; Li, Huiying (Frontiers in Veterinary Science, 2025)
This study investigated the effects of Periplaneta americana residue (PAR) on the growth performance and gut health of laying hens during the pre-breeding phase. Over an 11-week period, 450 one-month-old Nandan Yao chickens were assigned to six dietary groups in which PAR replaced 0%, 10%, 20%, 30%, 40%, or 50% of the soybean meal. The results revealed no significant impact of PAR on growth performance (p > 0.05). However, PAR supplementation significantly elevated duodenal and jejunal immunoglobulin A (IgA) levels, as well as ileal immunoglobulin M (IgM) and immunoglobulin G (IgG) levels (p < 0.05). Although no overall significant differences were observed in the villus height (VH), width (VW), crypt depth (CD), or the villus-to-crypt (V/C) (p > 0.05), ileal VH and V/C increased specifically in certain groups (p < 0.05). Additionally, ileal and jejunal pH values decreased significantly with increasing PAR levels (p < 0.05), and the intestinal microbiota diversity remained stable. Transcriptomic analysis revealed the regulatory roles of PAR in RNA biosynthesis, DNA repair, the immune response, and metabolic pathways. Overall, PAR incorporation modestly enhanced the growth performance and intestinal health in laying hens. These findings support PAR as an effective substitute for soybean meal in poultry diets, with a replacement ratio of 30% to 50%, growth performance, demonstrating optimal efficacy. This approach not only alleviates pressure on protein resources but also provides a scientific framework for valorizing insect-derived waste within circular agriculture systems.